A new species and new record of Samadinia Ng & Richer de Forges, 2013 (Crustacea: Brachyura: Epaltidae) from deepwater off north-eastern Queensland, Australia - Davie, Peter J. F.; Lee, Bee Yan (Zootaxa, 2023)
A new species of Samadinia Richer de Forges & Ng, 2013, is described from deep-water off northeastern Queensland, Australia. Samadinia hela n. sp. is distinctive in having pseudorostral spines longer than the maximum carapace length, slender preorbital spines that are curved inwards over the base of the rostrum, and long and laterally flattened hepatic and lateral bracnchial spine plates. A new record of S. despereaux (Lee, Richer de Forges & Ng, 2019) from Queensland is also reported in this study.